2015
DOI: 10.3177/jnsv.61.362
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Vitamin E-Deficient Mice Exhibit Cognitive Dysfunction via Elevation of Brain Oxidation

Abstract: Summary Vitamin E inhibits oxidative processes in living tissues. We produced vitamin E-deficient mice by feeding them a vitamin E-deficient diet to verify the influence of chronic vitamin E deficiency on cognitive function. We measured cognitive function over a 5-d period using the Morris water maze task, as well as antioxidant enzyme activity and lipid peroxidation in discrete brain regions, and total serum cholesterol content. Threeand six-mo-old vitamin E-deficient and age-matched control mice were used. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…In a previous study, vitamin E deficiency in mice increased serum cholesterol concentrations (47). Additionally, vitamin E has been shown to decrease endogenous cholesterol synthesis (48, 49) and it has been hypothesized that this effect may be due to a SREBP2-mediated downregulation of several genes implicated in the cholesterol synthesis pathway (50).…”
Section: Discussionmentioning
confidence: 86%
“…In a previous study, vitamin E deficiency in mice increased serum cholesterol concentrations (47). Additionally, vitamin E has been shown to decrease endogenous cholesterol synthesis (48, 49) and it has been hypothesized that this effect may be due to a SREBP2-mediated downregulation of several genes implicated in the cholesterol synthesis pathway (50).…”
Section: Discussionmentioning
confidence: 86%
“…Good sources of vitamin E are limited and found mainly in nuts, seeds, and oils. A study of vitamin E–deficient mice showed significant cognitive impairment relative to control mice, with evidence of greater lipid peroxidation products in the brain, suggesting that vitamin E deficiency may accelerate brain oxidation . However, human studies of cognitive status and vitamin E remain limited.…”
Section: Vitamin Ementioning
confidence: 99%
“…A study of vitamin E-deficient mice showed significant cognitive impairment relative to control mice, with evidence of greater lipid peroxidation products in the brain, suggesting that vitamin E deficiency may accelerate brain oxidation. 65 However, human studies of cognitive status and vitamin E remain limited. There is some observational evidence of protective effects of vitamin E intake or plasma status against cognitive decline.…”
Section: Vitamin Ementioning
confidence: 99%
“…In addition, studies in mice show that VitE deficiency causes cognitive decline, which is associated with increased lipid peroxidation within the brain [15,16]. However, results from human trials examining the efficacy of VitE supplementation for the treatment of dementia have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%